Statement to the Forty-Seventh Session of the United Nations General Assembly - King, Maurice A. (Permanent Mission of Barbados to the United Nations New YorkUS, 1992)
Addresses a number of cultural issues e.g. current development in Yugoslavia and Somalia. Expresses support by the UN in creating secure conditions for humanitarian action. Stresses the need for permanent enforcement tools to be put in place and for peace-keeping operations to be placed on a sound financial footing. Supports the view that peace and economic and social wellbeing are indivisible and that issues relating to development must be given.